Monitoring Aerosol Optical Depth for Air Quality Through Himawari-8 in Urban Area West Java Province Indonesia - Ridwana, Riki; Himayah, Shafira; Rabbi, Muh Fiqri Abdi; Ahmad Lugina, Izma Maulana; Al Kautsar, Azhari; Sakti, Anjar Dimara (Universitas Negeri Medan, 2023)
Air quality is a crucial parameter in human life. One air quality indicator can be observed through Aerosol Optical Depth (AOD). If these substances are pollutants such as particulate matter, aerosols, and ozone, it is confident that air quality will deteriorate, threatening human health and causing climate change. AOD monitoring can be used as a basis for policymakers and related parties to maintain the stability of air quality in the atmosphere. Many ground observation stations monitor air quality by obtaining data on PM2.5 and PM10 aerosol particles. However, the number of ground stations is limited, resulting in incomplete data. Fortunately, remote sensing satellites have the advantage of covering large areas and providing continuous observations, with the ability to gather information on large-scale aerosol and obtain spatiotemporal distribution. Therefore, this research aims to obtain AOD through Himawari-8 and analyze the spatiotemporal air quality in urban areas of West Java based on AOD. The research methodology used in this study is descriptive analysis with an empirical research approach. Assisted by remote sensing technology and Geographic Information Systems, this research generates AOD data extraction that can be obtained from the new generation satellite of Himawari-8. The distribution of AOD levels and spatiotemporal monitoring in urban areas of West Java is very dynamic depending on anthropogenic activity in a particular area and time. Keywords: Aerosol Optical Depth (AOD), Air Quality, Himawari-8